Effects of aluminum, copper and titanium nanoparticles on the liver antioxidant enzymes of the Nile fish (Oreochromis niloticus). (December 2020) - Canli, Esin G.; Canli, Mustafa
Abstract: The unique characteristics of metal-oxide nanoparticles (NPs) have made them demanded materials in many nanotechnological areas including the energy sector. Therefore, environmental fate of NPs should be understood and toxic levels should be set before releasing them into the environment. Thus, this study was conducted to investigate the effects of Al2 O3, CuO and TiO2 NPs on liver enzymes belonging to the antioxidant system such as glutathione peroxidase (GPx), glutathione reductase (GR), glutathione S-transferase (GST), superoxide dismutase (SOD) and catalase (CAT). Fish were first exposed to NPs (0, 1, 5, 25 mg/L) for 14 days and then they were allowed to survive in NP-free mediums for additional 14 days. After NP exposures, CAT and SOD activities decreased, whereas GST activity increased (P<0.05). However, there was no significant (P>0.05) alteration in GR and GPx activities. Transmission electron microscope (TEM) images demonstrated that all NPs accumulated in liver tissues after 14 days of exposure and they were mostly depurated after 14 days of elimination period. This study demonstrated that NPs accumulated in the liver caused oxidative stress in fish. It also suggests that environmental fates of NPs should take place in the environmental monitoring programs, as they seem potential pollutants for the future.